Mobile learning evolution: a decade of developments (2014-2023) - Mariia A. Kyslova; Serhiy O. Semerikov; Kateryna I. Slovak (Educational Technology Quarterly)
The rapid evolution of mobile technologies has significantly transformed educational landscapes over the past decade. This systematic review examines the development of mobile learning environments from 2014 to 2023, analyzing their conceptual foundations, theoretical frameworks, design principles, implementation strategies, and effectiveness. Building on our earlier taxonomy of learning environments, we propose an expanded framework that accommodates emerging technologies and pedagogical approaches. Through a comprehensive analysis of 97 articles published in peer-reviewed journals, we identify key trends in mobile learning research, including the integration of artificial intelligence, extended reality technologies, and learning analytics. Meta-analytic findings demonstrate moderate to significant positive effects of mobile learning on student outcomes across different educational levels and subject domains. The review further reveals that pedagogical approaches such as project-based learning, collaborative learning, and situated learning significantly enhance the effectiveness of mobile learning environments. We also examine challenges in implementation, including technological barriers, pedagogical integration issues, and concerns about equity and accessibility. The paper concludes with a proposed research agenda and practical guidelines for developing effective, inclusive, and sustainable mobile learning environments in the emerging educational technology landscape.